Transforming the Learning Environment of Undergraduate Physics Laboratories to Enhance Physics Inquiry Processes - Gregory P. Thomas; Al Meldrum; John Beamish (Karolinum Press, 2017)
Concerns persist regarding the lack of promotion of students' scientific inquiry processes in undergraduate physics laboratories. The consensus in the literature is that, especially in the early years of undergraduate physics programs, students' laboratory work is characterized by recipe type, step-by-step instructions for activities where the aim is often confirmation of an already well-established physics principle or concept. In response to evidence reflecting these concerns at their university, the authors successfully secured funding for this study. A mixed-method design was employed. In the 2011/2012 academic year baseline data were collected. A quantitative survey, the Undergraduate Physics Laboratory Learning Environment Scale (UPLLES) was developed, validated, and used to explore students' perceptions of their physics laboratory environments. Analysis of data from the UPLLES and from interviews confirmed the concerns evident in the literature and in a previous evaluation of laboratories undertaken in 2002. To address these concerns the activities that students were to perform in the laboratory section of the course/s were re/designed to engage students in more inquiry oriented thinking and activity. In Fall 2012, the newly developed laboratory activities and tutorials, were implemented for the first time in PHYS124; a first year course. These changes were accompanied by structured training of teaching assistants and changes to the structure of the evaluation of students' laboratory performance. At the end of that term the UPLLES was administered (n = 266) and interviews with students conducted (n = 16) to explore their perceptions of their laboratory environments. Statistically significant differences (p<.001) between the students in the PHYS 124 classes of 2011/2012 and 2012/2013 across all dimensions were found. Effect sizes of 0.82 to 1.3, between the views of students in the first semester physics classes of 2011/2012 and 2012/2013, were also calculated suggesting positive changes in the laboratory inquiry orientation. In their interviews, students confirmed and detailed these positive changes while still noting areas for future improvement.